EVALUASI ATAS PENERAPAN SISTEM AKUNTANSI SATUAN KERJA PENGELOLA KEUANGAN DAERAH PEMERINTAH KOTA BOGOR (Studi Kasus pada Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah) - ., Jeffry (STIE Binaniaga, 2012)
Aim from this research has explained how far regulation that applied by city government in Bogor, explain how far accounting system applications SKPKD in city government in Bogor , and explain financial statement presentation in city government in Bogor. Research method that used case study method. This method covers activity that done with hold direct research to location to gets data that need to relate to problem that canvassed. Research is done Dinas Pendapatan, Pengelolaan Keuangan, dan Aset Daerah Kota Bogor. From research result that done, that city government bogor in the year 2007 apply Permendagri number 13 year 2006. Then setting accountancy wisdom in city local government bogor appointed in number mayor regulation 26 year 2008 that published on 25 novembers 2008 about system and region finance accounting procedure. City local government finance accounting system bogor comprehensively apply cash inflow accounting procedure, money supply expenditure accounting procedure, perosedur asset accountancy, with accounting procedure besides money supply. Financial statement presentation event, city government financial statement bogor fulfil Standard Government Accountancy as that regulated in PP number 24 year 2005. Evaluation result in this research that city government region finance manager work unit accounting system bogor as according to Permendagri number 13 year 2006 then done to setting accountancy wisdom that regulated in number mayor regulation 26 year 2008. Even if happen slowness in regional leader regulation publication but system and region finance accounting procedure based on Permendagri number 13 year 2006 permanent applied at the (time) of regional leader regulation arrangement current.Keyword: accounting system, ministry of home affairs regulation (Permendagri)